The great unexpected - Creech, Sharon (New York : Joanna Cotler Books, 2012)
"In the little town of Blackbird Tree live two orphan girls: one Naomi Deane, brimming with curiosity, and her best friend, Lizzie Scatterding, who could talk the ears off a cornfield. Naomi has a knack for being around when trouble happens. For she knows all the peculiar people in town--like Crazy Cora and Witch Wiggins and Mr. Farley. But then, one day, a boy drops out of a tree. The strangely charming Finn boy. Then the Dingle Dangle man appears, asking all kinds of questions. Curious surprises are revealed--three locked trunks, a pair of rooks, a crooked bridge, and that boy. Soon Naomi and Lizzie find themselves zooming toward a future neither could ever have imagined. Meanwhile, on a grand estate across the ocean, an old lady whose heart has been deceived concocts a plan. . . "--Publisher.
Keywords: Orphans -- Juvenile fiction; Ireland -- Juvenile fiction; Orphans -- Fiction; Ireland -- Fiction